THE INFLUENCE OF PSYCHOLOGICAL CONTRACTS ON PT. XYZ INNOVATIVE WORK BEHAVIOR WITH WORK ENGAGEMENT AS MODERATOR - Dany Efendi; Udisubakti Ciptomulyono; Bustanul Arifin Noer (LPSDI Bina Patria, 2024)
This research goals to know the impact of the psychological contract on Innovative Work Behavior, and how the role of work engagement moderates this relationship. The population at PT XYZ is 110 workers. Sampling was taken using the simple random sampling method. This study uses a statistical method called Partial Last Square to analyze the influence and moderation of Innovative Work Behavior. The study findings are that the Psychological Contract in the Relational Contract and Transactional Contract Dimensions has a significant impact on Innovative Work Behavior. Work Engagement is able to significantly moderate the relationship between the Psychological Contract on the Relational and Transactional Contract Dimensions on Innovative Work Behavior. This study aims to enrich the existing literature on psychological contracts, innovative work behavior, and work engagement. The primary objective is to explore the intricate relationships between these constructs and how they collectively influence organizational outcomes. By delving into these relationships, the research seeks to provide valuable insights and practical recommendations for human resource management practices.